Modern features of the management of gastrointestinal food allergy in children - Yu.R. Chernysh; O.M. Okhotnikova (Zdorovʹe Rebenka, 2018)
Food allergy affects millions of people, reduces the quality of life, can lead to fatal consequences, it is a serious problem for society. Today, much attention is paid to the researches on the development of optimal preventive measures to reduce the prevalence of food allergy. Until recently, it was believed that it was necessary to avoid the most common food allergens during pregnancy and breastfeeding for the prevention of food allergy in children. However, there is evidence that the early impact of potential food allergy can reduce the risk of food allergy developing. No special diet during pregnancy or for the lactating mother, exclusively breastfeeding for 4–6 months. It is recommended not to avoid the introduction of solid products after 46 months of life, even for children at high risk of allergic diseases. The clinical management of food allergy includes interventions to manage acute reactions and long-term strategies to minimize the risk of further reactions (dietary modification, education and measures approaches to avoid allergens and pharmacological and non-pharmacological management strategies). The article considers approaches to the management of children with gastrointestinal food allergy. At this time, the standard measures in the management of such patients are the elimination diet, control of systemic reactions caused by food allergens. Avoid using known food triggers is the main approach to the primary treatment of immunoglobulin (Ig) E-mediated gastrointestinal food allergy. Topical glucocorticosteroids remain the first-line drugs in the treatment of eosinophilic esophagitis. There are many controversial issues of managing children with non-IgE-mediated gastrointestinal food allergy. There is a need for new researches to develop effective therapeutic and prophylactic measures for managing patients with common and complex problem such as food allergy.